AB0264 STAT4 RS7574865 Gene Polymorphism is not Associated with Severe Disease Phenotype and Response to Tumor Necrosis Factor-α Inhibitor Treatment in Patients with Rheumatoid Arthritis. (9th June 2015) - Ozen, G.; Saglam, B.; Odabasi, A.; Ozluk, O.; Yentur, S.P.; Saruhan-Direskeneli, G.; Inanc, N.; Direskeneli, H.
Abstract : Objectives: To investigate the association between single nucleotide polymorphism (SNP) of rs7574865 in signal transducer and activator of transcription 4 ( STAT4) gene and RA susceptibility among the Turkish population and to determine the effects of this genetic variant on disease characteristics and response to tumor-necrosis factor-α inhibitor (TNFi) treatment. Methods: rs7574865 SNP of STAT4 was genotyped in a total of 389 Turkish RA patients fulfilling the 1987 ACR classification criteria (F/M: 324/65, mean age: 52.8±12.6 years, 66.8% RF positive) and 573 healthy controls (F/M: 248/275, mean age: 30.1±9.9 years). Retrospectively, along with disease characteristics, EULAR response to biologic DMARDs, especially TNFi, DAS28 scores of each visit during the entire follow-up of RA patients (complete disease activity data were obtained from 318 patients) were recorded. Results: The genotype distribution showed that RA cohort (GG: 297 [76.3%], GT: 79 [20.4%], TT: 13 [3.3%] patients) had significantly higher rate of TT genotype compared to HC (GG:431 [82.4%], GT:84 [16.1%], TT: 8 [1.5%] individuals) ( P =0.04). Presence of T minor allele (GT or TT genotype) was also significantly higher in RA patients (23.7% vs 17.6%, OR=1.44; CI:95% 1.042-1.99, P =0.03). However, T allele carrier rates of seronegative (16.9%) and seropositive (25.6%) (either RF or Anti-CCP) patients were similar ( P =0.14). Biologic treatment requirements, extra-articular involvement and joint surgery rates were similar in RA patients with and without T allele (Table 1 ). During 6.0±4.0 years follow-up period, in a median of 10 (min-max: 2-42) visits, the ratio of visits in moderate-high disease activity and remission-low disease activity and sustained remission rate (remission in 3 consecutive visits) were not different in patients with and without T allele (Figure 1 ). Of the 161 patients treated with biologic DMARDs, 141 received TNFi (infliximab 51, adalimumab 47, etanercept 43 patients) and the EULAR response to TNFi at 6th month were also similar in T allele carrier and non-carrier patients (59.3% vs 71.9%, P =0.19). Seropositivity for either RF or anti-CCP (82.4% vs 80.5%), disease durations (13.9 vs 14.3 years) and baseline DAS28 scores (5.34 vs 5.31) were also comparable in TNFi responders and nonresponders. Conclusions: The data revealed that T allele of STAT4 rs7574865 was associated with an increased risk of RA in Turkish population. However presence of T allele does not seem to have an effect on disease phenotype and TNFi response. Disclosure of Interest: None declared